Techno-Economic Analysis of Cement Decarbonization Techniques: Oxygen Enrichment vs. Hydrogen Fuel - Bruno C. Domingues; Diogo M. F. Santos; Margarida Mateus; Duarte Cecílio (Hydrogen, 2024)
The Paris Agreement aims to limit global warming, and one of the most polluting sectors is heavy industry, where cement production is a significant contributor. This work briefly explores some alternatives, recycling, reducing clinker content, waste heat recovery, and carbon capture, discussing their advantages and drawbacks. Then, it examines the economic viability and benefits of increasing oxygen concentration in the primary burning air from 21 to 27 vol.%, which could improve clinker production by 7%, and the production of hydrogen through PEM electrolysis to make up 5% of the fuel thermal fraction, considering both in a cement plant producing 3000 tons of clinker per day. This analysis used reference values from Secil, an international company for cement and building materials, to determine the required scale of the oxygen and hydrogen production, respectively, and calculate the CAPEX of each approach. It is concluded that oxygen enrichment can provide substantial fuel savings for a relatively low cost despite a possible significant increase in NOx emissions. However, hydrogen production at this scale is not currently economically viable.